THE MARKERS OF OXIDATIVE STRESS IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION WITH NON-ALCOHOLIC FATTY LIVER DISEASE - I. E. Belaya (Российский кардиологический журнал)
Aim. To study plasma lipid profile, systemic inflammation and endotelial function in patients with acute period of MI with Q-wave and liver steatosis (LS) or non-alcoholic steatohepatits (NASH).Material and methods. Totally 48 patients with acute MI of the left ventricle were studied (1st group), with average age 66,33±1,66; 53 — with acute MI and LS (2nd group) — average age 63,74±1,87, and 7 — with acute MI and NASH (3rd group) — average age 58,86±4,47. In all groups men dominated. We measured the levels of liver enzymes, bilirubin, total cholesterol, LDP cholesterol, VLDL cholesterol, triglycerides, atrogenity coefficient, cholesterol-accepting properties of HDL, level of nitrite- and nitrate-anions in serum, hsC-reactive protein. Results. The disordered lipid profile in patients of both groups shows the increased levels of total cholesterol, LDL (p<0,001) and VLDL (p<0,01), atherogenity coefficient (p<0,001) and lowering of HDL and their cholesterol-accepting properties (p<0,001). In patients of 2nd and 3rd groups there is an increase of nitrites (p<0,001) and nitrates (p<0,001). Endothelial dysfunction was the worse in acute MI with NASH. In patients with combined pathology there is increase of C-reactive protein (p<0,001). The parameter of systemic inflammation is higher in patients with acute MI with NASH.Conclusion. In patients with combined MI and LS or NASH there is an increase of atherogenity and decrease of anti-atherogenity in lipid profile, increase of stable NO metabolites with maximally prominent endothelial dysfunction in patients with NASH, due to aseptic inflammation. Marker of inflammation severity is higher in those with NASH comparing to LS.